Investigation of different electrochemical cleaning methods on contaminated healing abutments in vitro: an approach for metal surface decontamination - Thiha Tin Kyaw; Takao Hanawa; Shohei Kasugai (SpringerOpen, 2020)
Abstract Background To evaluate the effects of electrolysis on cleaning the contaminated healing abutment surface and to detect the optimal condition for cleaning the contaminated healing abutment. Methods Ninety healing abutments removed from patients were placed in 1% sodium dodecyl sulfate solution and randomly divided for electrolysis with 7.5% sodium bicarbonate in the following three different apparatuses (N = 30): two stainless steel electrodes (group I), a copper electrode and a carbon electrode (group II), and two carbon electrodes (group III). The samples were placed on cathode or anode with different electric current (0.5, 1, and 1.5 A) under constant 10 V for 5 min. Electrolyte pH before and after electrolysis were measured. Then, the samples were stained with phloxine B and photographed. The proportion of stained areas was calculated. The surface was examined with a scanning electron microscope (SEM) and energy-dispersive X-ray spectroscopy (EDS). Results Electrolyte pH decreased after electrolysis at 1 A and 1.5 A in group I and II. Applying cathode at 1 A in group III, the amount of residual contamination was the lowest in all the conditions examined in the present study. SEM images revealed that applying cathode at 1.5 A in group I induced a rough surface from the smooth surface before the treatment. EDS analysis confirmed that the surfaces treated on cathode at 1 A in group III revealed no signs of organic contamination. Conclusion Electrolysis of using carbon as electrodes, placing the contaminated healing abutments on cathode, and applying the electric current of 1 A at constant 10 V in 7.5% sodium bicarbonate could completely remove organic contaminants from the surfaces. This optimized electrochemical cleaning method seems to be well worth investigation for the clinical management of peri-implant infections.